Design and Optimization of Open Truss Interlaced Composite Structures - Liao, Chengqian (Université d'Ottawa / University of Ottawa, 2022)
This thesis discusses the optimization of non-periodic open structure continuous-fibre PMFRC parts where yarns extend along 3D paths that maximize the specific structural performance of the resulting part for specific load cases. The work focuses on optimizing the geometry of dry yarn structures using steepest ascent (SA) methods and calculating structural performance of the resulting PMFRC parts using finite element analysis (FEA).
Keywords: open truss; composite structures; interlacing